(untitled) (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted to study on the performance of 76 lentil genotypes that are suitable to cultivate under the southern belt of Bangladesh (AEZ13). The experiment was laid out in RCBD with three replications. Correlation coefficient was done to identifying the best relationship among the characters and path coefficient was also used to determine the direct and indirect relationships between yield and certain characters in 76 lentil genotypes. The data were analyzed statistically and means were adjudged by DMRT at 5% level of probability. Results revealed that genotypes had a significant control in all the studied characters at 1% level. Among the genotype, BD3818 requiring more time for plant maturity (102.50 days) while it was also recorded the maximum pods and seeds (154.90 plant1 and 2.0 pod-1, respectively) as well as higher grain yield (173.70 g line1 plot1). So the genotype BD-3818 would be most suitable productive genotype and may be useful in improving seed yield of lentil under the southern belt of Bangladesh (AEZ-13). Correlation coefficient and path analysis also revealed that highly significant positive correlations were detected between first and 50% flowering (r= 0.925**) and also between grain yield and biological yield (r = 0.821**) while path analysis demonstrated that grain yield had the highest positive direct effects (0.8373) and the higher negative direct effect was -0.1904 in respect of days to 50% flowering with an average residual effect of 0.2839. Above result indicated that 50% flowering is the main yield contributing traits and it suggested that the delay flowering significantly increased the grain yield. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22162 J. Environ. Sci. & Natural Resources, 7(1): 139-144 2014